2020
DOI: 10.1158/0008-5472.can-19-1033
|View full text |Cite
|
Sign up to set email alerts
|

USP22 Functions as an Oncogenic Driver in Prostate Cancer by Regulating Cell Proliferation and DNA Repair

Abstract: Emerging evidence indicates the deubiquitinase USP22 regulates transcriptional activation and modification of target substrates to promote pro-oncogenic phenotypes. Here, in vivo characterization of tumor-associated USP22 upregulation and unbiased interrogation of USP22-regulated functions in vitro demonstrated critical roles for USP22 in prostate cancer. Specifically, clinical datasets validated that USP22 expression is elevated in prostate cancer, and a novel murine model demonstrated a hyperproliferative ph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 60 publications
3
39
1
Order By: Relevance
“…Another focus of the current study, the USP22 protein is a member of the deubiquitinase family, which comprises of more than 70 members (McCann et al, 2020). USP22 has further been correlated with enhanced intestinal tissue regeneration following intestinal I/R injury (Ji et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Another focus of the current study, the USP22 protein is a member of the deubiquitinase family, which comprises of more than 70 members (McCann et al, 2020). USP22 has further been correlated with enhanced intestinal tissue regeneration following intestinal I/R injury (Ji et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…USP22 promotes the advance of gastric cancer by stabilizing BMI1 protein [129]. Also, USP22 plays a carcinogenic effect in prostate cancer by regulating cell proliferation and DNA repair [130]. The active site residues of Ubp8 are catalytically well-arranged in the absence of ubiquitin [119,121,124].…”
Section: Ubp8 Needs Partner Proteins For Activitymentioning
confidence: 99%
“…Depletion of USP22 sensitizes cells to genotoxic insult; analysis of the USP22-sensitive ubiquitylome identified the nucleotide excision repair protein, XPC, as a critical mediator of the USP22-mediated response to genotoxic insult. [36] Knockdown of E6AP in DU145 cells and analysis of a proteome.…”
Section: Ubiquitinationmentioning
confidence: 99%
“…Of these, DEK stabilization was shown to promote prostate epithelial cell invasion [38]. Other proteome studies revealed clusterin as a novel target of E6AP with roles in cell growth [37] and XPC, as a critical mediator of the USP22-mediated response to genotoxic insult [36] (Table 1).…”
Section: Ubiquitinationmentioning
confidence: 99%